Simulation of free turbulent particle-laden jet: evaluation of first-order turbulence models and stochastic dispersion models. (11th February 2010) - Boughattas, N.; Gazzah, M-H.; Habli, S.; Cabot, M-S.; Said, R.
This paper is devoted to the numerical and theoretical study of free turbulent glass particle-laden jets. This study is based on results from a hybrid Euler/Lagrange simulation. Five two-equation turbulence models (STD k-ε, RNG k-ε, k-ω (88), k-ω (98) and MTS) were investigated and applied to the carried phase field simulation. Two stochastic particle dispersion models (Eddy Interaction Model and Time Correlated Model) were employed for the prediction of the particulate phase. Numerical results were compared with available experimental measurements. It was found that MTS and k-ε models predictions agree better with experimental measurements than those of the other models. The results show also that the Time Correlated Model provides improved fluctuating results in comparison to the Eddy Interaction Model. In contrast, the EIM provides better results for simulating mean particle velocity.